What World is This? A review of Judith Butler’s What World is This? A Pandemic Phenomenology - Brewer, Marta (Hybris, 2023)
The article looks at Judith Butler’s 2022 book titled What World is This? A Pandemic Phenomenology: an attempt to analyse the pandemic using the phenomenology of Max Scheler, Maurice Merleau-Ponty, as well as feminist phenomenology. The author of the book considers what the pandemic reveals about our being-in-the-world and what interdependencies it brings to light. She points out the political and ethical implications of thinking based on a common immune problem and the need for change through striving for radical equality.